TEKNIK ANALISA STRUKTUR DAN KOMPONEN BIOFILM PADA PENGOLAHAN AIR DAN AIR LIMBAH - Hamidah, Laily Noer (Journal of Research and Technology, 2015)
Biofilm is proven to be effective to be used in water and wastewater treatment. Different raw water’s organic compound contents will affect to the heterogenity of the biofilm. This heterogenity is caused by different abilities of the microbial biofilm constituent in decomposing organic coumpound in raw water. Analysis of structures and components can be done to study the heterogenity of the biofilm. This analysis is not only able to describe the quantity but also the quality of the biofilm. The purpose of this review is to compare the various techniques in analyzing the structure and components of the biofilm. Analysis techniques can be performed with image analysis, chemical analysis, biochemical and population analysis. Method that commonly used is the image analysis by Scanning Electron Microscopy (SEM) to observe the structure of the biofilm. Chemical analysis using colorimetry, and analysis of total protein is using Lowry’s method and Bradford’s method, and molecular analysis by PCR that is used to characterize the components of biofilm’s constituent.